Pengaruh Konsentrasi Liquor Kakao (Theobroma cacao L.) terhadap Karakteristik Krim Berbahan Aktif Ekstrak Kunyit dan Daun Asam - Rusiyantoro, Monica; Mulyani, Sri; Arnata, I Wayan (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 9 No 2 (2021): JuniDO - 10.24843/JRMA.2021.v09.i02.p09, 2021)
The concentrations of cocoa liquor is an alternative to increase phenolic compounds and at the same time as a natural coloring agent in creams. This study aims to determine the effect of the concentration of the cocoa liquor on the characteristics of the cream with the active ingredient of turmeric and tamarind leaves and to determine the cocoa liquor concentration to produce the best characteristics of the cream with the active ingredient of turmeric and tamarind leaves. This study used a randomized block design with 6 levels of cocoa liquor concentration of 0%, 4%, 6%, 8%, 10%, and 12%. The variables observed were homogeneity, viscosity, pH, spreadability, separation ratio, adhesion, L*, a*, b* color test, and total phenol of the cream. The results showed that the treatment of cocoa liquor concentration had a very significant effect on pH, viscosity, adhesion, dispersion, L*, a*, b* color tes, total phenol test, and organoleptic color test. Meanwhile, the treatment of cocoa liquor concentration had a significant effect on the separation ratio of the cream with the active ingredient of turmeric and tamarind leaf. The results of this study indicate that the concentration of cocoa liquor as much as 4% produces a cream with the active ingredient of turmeric and tamarind leaves with the best characteristics that are homogeneous with pH 6.13, viscosity 15333cp and, adhesion 2.39sec, spreadability 7.18cm, separation ratio 0.95, color test values L * 15.39, the values of a * 11.55, the values of b * 13.92, with the organoleptic test for color preferences 5.1. Keywords: Liquor cacao, turmeric, tamarind leave, cream characteristics